2021
DOI: 10.1038/s41598-021-02987-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic peripheral vestibular disorders (excluding positional vertigo) in workers following head injury

Abstract: Benign paroxysmal positional vertigo has typically been reported to be the most common cause of post-traumatic dizziness. There is however paucity in the literature about other peripheral vestibular disorders post-head injury. This article provides an overview of other causes of non-positional dizziness post-head trauma from our large institutional experience. The UHN WSIB Neurotology database (n = 4291) between 1998 and 2018 was retrospectively studied for those head-injured workers presenting with non-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Use of oVEMPs to test utricular dysfunction in TBI has rarely been reported. Campbell et al described asymmetrical oVEMPs in five of 29 (17%) of patients with chronic TBI, which was not significantly different from age-matched controls ( 31 ), whereas Misale et al reported abnormalities in 18 of 36 patients (50%) with TBI and non-positional, post-traumatic episodic vertigo ( 33 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Use of oVEMPs to test utricular dysfunction in TBI has rarely been reported. Campbell et al described asymmetrical oVEMPs in five of 29 (17%) of patients with chronic TBI, which was not significantly different from age-matched controls ( 31 ), whereas Misale et al reported abnormalities in 18 of 36 patients (50%) with TBI and non-positional, post-traumatic episodic vertigo ( 33 ).…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our findings, abnormality rates on either test are often < 25% with few reports of bilateral involvement ( 4 , 12 , 13 , 29 31 ). Three studies which included vertical canal vHIT showed increased detection rates with reports of abnormal function of at least one semicircular canal in 21.2–52% of patients ( 12 , 32 , 33 ). Otolith function has been mainly studied using cVEMPs with rates of saccular dysfunction ranging between 0 and 52% ( 7 , 12 , 13 , 29 , 31 , 33 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benign paroxysmal positional vertigo, labyrinthine concussion, and vestibular migraine are the most common etiologies of peripheral vestibular system disorders reported after mTBI [ 25 ]. Direct vestibular nerve or labyrinth injury resulting from petrous bone fracture, potentially generating a perilymphatic fistula, has also been associated with CCT to a lesser extent [ 70 71 ]. More recently, a case series pointed out that CCT may also potentiate superior semicircular canal dehiscence syndrome [ 72 ].…”
Section: Post Traumatic Craniocervical Disorders Reviewed From a Post...mentioning
confidence: 99%
“…There is evidence that these systems are often affected in the acute phase after mmTBI [ 8 , 9 ]. In the chronic phase after mmTBI, failure to compensate for a peripheral vestibular disruption may cause persistent dizziness [ 10 ]. A recent study by Campbell et al [ 11 ] found that persisting dizziness and balance problems after mmTBI can be explained by dysfunction in central sensory integration rather than dysfunction in the peripheral vestibular or oculomotor systems.…”
Section: Introductionmentioning
confidence: 99%